NUMERICAL STRENGTH OPTIMIZATION OF STRUCTURAL DESIGN MADE OF DATE PALM FRONDS LEAVES WOOD PARTICLEBOARD - Ali Hussein, Rahman; Ali Nasser, Mohammed; Kadhim Jawad, Labed; Kadhim Mejbel, Mohanad (Journal of Applied Engineering Science, 2022)
Particleboard is a good substitute for costly wood/plywood boards. Particleboard can be developed from Date-Palm Leaves (DPL) as an annually renewable agro waste. DPL has a higher ultimate fiber length (1.25-2.50 mm) and higher α-cellulose content (about 60%) than hardwood/plywood and jute stick. In this present research, a numerical analysis focused on predicting the optimum strength for a selected chair style based on the mechanical strength behavior of the date palm leaves particleboard. This analysis is based on employing a chair model generated by Solidworks software and simulated by ANSYS software using the experimental mechanical properties of the selected material. Results show that the numerical analysis can predict a precise strength and safe behaviour for the selected chair shape and size according to the material properties without the manufacturing process taking part.